Políticas de educação rural no Estado de São Paulo (1889-1994): disputas e conflitos de classe pela hegemonia no bloco no poder - Junqueira, Victor Hugo (Universidade Federal de São Carlos, 2018)
At the beginning of the 21st century, rural education became a hegemonic expression within social movements and state politics. In this context, rural education has become synonymous with backwardness, precariousness of schools, and sometimes conservative because it is tied to the interests of the ruling classes and imposed by the government on workers spreading an urbanist knowledge, or in the most recent period related to the interests of agribusiness for instrumentalization of the workers to work in the field. The distinction made in the political-theoretical debate dichotomized educational policies aimed at the rural population between those linked to the interests of capital and the rural state and those related to the interests of the workers. However, within the framework of class society, in which education assumes a universalist character, this distinction is not so simple, since it implies identifying which economic interests and which power relations support certain policies. From this understanding, it is possible to question: what is the role of educational policies directed at the rural population in the set of social relations of production? What power relations materialized in state apparatuses favored or limited rural education policies? Based on these questions the objective of this thesis is to analyze the development of rural education policies and the conditions of school attendance for the rural population in the state of São Paulo between the end of the nineteenth century and the beginning of the 1990s, from the economic transformations and the role of the state in reproducing conditions and social relations of production. In other words, the pretension is to emphasize how the material conditions of intensification of the capitalist relations of production and the contradictions present in the constitution of the bourgeois state were related to the politics of schooling of the rural population. Methodologically, besides the bibliographical revision, the research examined primary sources, such as the newspapers Correio Paulistano, Diário Nacional, O Combate, Diário de S. Paulo, Terra Livre, Jornal dos Sem Terra, reports of the presidents of the states (1900-1929), and after that, from the Governors of State (1936-1966), Education Yearbooks (1914, 1918, 1919, 1922, 1926, 1936-1937), as well as statistical data and information produced by state agencies such as the Fundação Seade, the Instituto de Pesquisas Econômicas Aplicadas (IPEA) and Instituto Brasileiro de Geografia e Estatística (IBGE). The results confirm the hypothesis raised that the state politics of rural education in the state of São Paulo are part of the project of formation of bourgeois society in Brazil, whose intensity of movement (expansion - retraction) is not determined strictly by the needs of the development of the forces productive in the countryside, but also by the ideological and productive role of education for the affirmation of social relations and capitalist conditions of production, in the face of the advance of industrialization. This process reveals, however, a series of contradictions that permeate the power relations between the different class fractions, materialized in state politics.
Rural education politics in the State of São Paulo (1889-1994): disputes and class conflicts by hegemony on the block in power
Keywords: Educação rural; Estado.; Políticas educacionais; História da Educação; Estado de São Paulo; Rural education; State; Educational politics; History of Education; State of São Paulo; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO